ACE Gene Mutations (rs577350502) in Early-Onset and Recurrent Myocardial Infarction: A Case Report and Review - Deng X; Guo X; Chen X; Zeng X; Guo J; Bai X; Zhang P; Wang Y (Dove Medical Press, 2024)
Xiaoxi Deng,1,* Xiaofei Guo,1,* Xiaojie Chen,2 Xinyu Zeng,1 Jiamin Guo,1 Xin Bai,1 Ping Zhang,1 Yuan Wang1 1Department of Pathology, Wangjing Hospital, China Academy of Chinese Medical Sciences, Beijing, 100102, People's Republic of China; 2Department of Emergency, Wangjing Hospital, China Academy of Chinese Medical Sciences, Beijing, 100102, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuan Wang, Ping Zhang, Department of Pathology, Wangjing Hospital, China Academy of Chinese Medical Sciences, 6 Wangjing Zhonghuan South Road, Chaoyang District, Beijing, 100102, People's Republic of China, Tel +86 010-84739040, Email yuanwangwwwy@126.com; zhang787ping@126.comBackground: Acute myocardial infarction (AMI) is a severe acute coronary syndrome, demonstrating a trend toward affecting younger individuals in recent years. The association between early-onset myocardial infarction and single nucleotide polymorphism necessitates further exploration and evaluation.Case description: We present a case of a patient experiencing early-onset and recurrent myocardial infarction. The patient underwent stent implantation for myocardial infarction at the age of 53 and subsequently encountered two more myocardial infarctions within a span of 16 years. Following interventional therapy, genetic testing was conducted to assess the efficacy of subsequent anti-heart failure medications, with the aim to preemptively address heart failure risks. Genetic testing revealed a mutation in the angiotensin-converting enzyme (ACE) gene (rs577350502, g.63488533C>A), characterized by an intron-deletion single nucleotide variant.Conclusion: While this variant has not been previously reported to be associated with any specific disease, we hypothesize that it may contribute to the susceptibility and risk of myocardial infarction and coronary heart disease in the patient under consideration. This observation underscores the significance of investigating the insertion/deletion polymorphisms of the ACE gene in the context of AMI and emphasizes the necessity for further validation of this variant and other genetic markers associated with AMI in related diseases.Keywords: ACE, case reports, gene mutations, myocardial infarction, SNV